2014
DOI: 10.9790/4861-06125862
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nanostructured Thin Films of (CdS)0.6 Se0.4 for Solar Cell

Abstract: Abstract:The high quality thin films of (CdS) 0.6 Se 0.4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…In CdS/CdTe thin film solar cells, alloy formation has both beneficial and detrimental effects on device performance depending on how the alloys are formed, their composition and their compositional distribution. The proper amount of interdiffusion is necessary for a superior efficiency solar cell [8]. However, diffusion of CdS into CdTe is a faster process than that of CdTe into CdS, and is more difficult to control, especially for cell structures with ultra-thin, <100 nm, CdS films.…”
Section: Controlling Cds/cdte Interdiffusionmentioning
confidence: 99%
See 2 more Smart Citations
“…In CdS/CdTe thin film solar cells, alloy formation has both beneficial and detrimental effects on device performance depending on how the alloys are formed, their composition and their compositional distribution. The proper amount of interdiffusion is necessary for a superior efficiency solar cell [8]. However, diffusion of CdS into CdTe is a faster process than that of CdTe into CdS, and is more difficult to control, especially for cell structures with ultra-thin, <100 nm, CdS films.…”
Section: Controlling Cds/cdte Interdiffusionmentioning
confidence: 99%
“…Polycrystalline CdSxTe1-x and CdS1-yTey thin films can be produced by several methods such as: thermal evaporation (co-evaporation of CdS and CdTe) [7][8][9], RF magnetron sputtering [9], brush plating [10], pulsed laser deposition [11], pulse plating [12], closed space sublimation [13][14][15][16][17], metal organic chemical vapor deposition MOCVD [18], chemical bath deposition (CBD) [19], and spray pyrolysis [20][21][22] by first producing CdS films then annealing in Te atmosphere. It is well known that the properties of produced films are affected by the deposition technique and deposition parameters used, such as deposition rate, substrate temperature, and thickness of the films [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of structure, it has been reported that the CdS can exist in cubic (Zinc blend) phase [6][7][8][9][10][11], hexagonal phase of the two phases, depending on the method of preparations and the condition synthesis [12,13]. It has different commercial applications, such as solar cell [14], photo detector [15], LED [16], FET [17], pixel electronics and various semiconducting devices [18]. Various approaches were used to deposit the CdS thin films, comprising evaporation by vacuum [19], and chemical bath deposition (CBD) [20], sol-gel [21] and so on.…”
Section: Introductionmentioning
confidence: 99%